Space, Culture, and Escapism: Nightlife Venues at Bira Beach Bulukumba - Armi Indrayuni; Syamsu A. Kamaruddin; Arlin Adam; A Zulfikar Aliuddin (Jurnal Scientia, 2024)
This research aims to examine the phenomenon of escapism at Bira Beach, South Sulawesi, with the aim of understanding the complex interactions between night entertainment workers, tourists and local communities in a tourism context. By adopting a constructivist and interpretative paradigm, this study uses qualitative methods including direct observation and in-depth interviews to collect data. This approach allows research to gain a comprehensive understanding of how the social and cultural reality at Bira Beach is constructed and handled through the practice of escapism. The research results show that escapism at Bira Beach acts as a mechanism of adaptation and resistance to social norms and economic pressures, while influencing social structure and local identity. This phenomenon is analyzed through the lens of relevant sociological theories: Pierre Bourdieu with the concept of "habitus" which explains how social structures and external conditions shape individual perceptions and actions; Erving Goffman with his dramaturgical theory which allows an understanding of how individuals play various social roles as a form of escapism; and Peter L. Berger and Thomas Luckmann whose social construction theory helps describe how social and cultural realities are created through continuous interactions between individuals. The conclusion of this study emphasizes that escapism at Bira Beach not only impacts individual experiences, but also has broad implications for social and cultural structures. Tourism and escapism, as social and economic phenomena, play a critical role in shaping and changing the dynamics of local communities, creating challenges and opportunities that must be managed with an approach that is inclusive and sensitive to social and cultural aspects. This research reveals that a deep understanding of the interactions between structure and agency is critical to facilitating harmonious sustainable development between visitors and local communities.